Ocalenie Republiki. Charles de Gaulle wobec tradycji republikańskiej (1940-1946) - Ujazdowski, Kazimierz M. (Czasopismo Prawno-Historyczne, 2018)
Contrary to the common belief, the Fifth Republic could not be established as a Republican monarchy. In France the idea of a republic was created by the French Revolution and its values were shaped in the fundamental confrontation with the monarchist tradition. The specifically understood idea of a nation’s sovereignty the formation of which was influenced by Rousseau’s though, as well as the ideas of the indivisibility and lay character of the republic, constituted a completely new model of statehood. In such a situation, the synthesis of antagonistic traditions was not possible. Although de Gaulle had been brought up in a family of pro-monarchist attitudes, he followed the state patriotism idea and was a supporter of the Republic as a durable basis for France’s existence. His views matured under the influence of French Republican nationalists Charles a Peguy and Maurice Barres, who inspired young de Gaulle and shaped his state patriotism. Later in his life de Gaulle’s idea was not so much to reconcile the monarchist and the republican tradition, but to create a republic that would integrate different families of ideas. This concept was also induced by manner of understanding the role of Christian obligations due to the public sphere. Following the spirit of the Catholic-liberal “Correspondent” de Gaulle believed that in the world shaped by the Revolution’s heritage Christian ideas do not need to be deemed to be defeated. During World War II, de Gaulle, then the leader of Free France, consistently strengthened the French Republican tradition in the Vichy dispute. In the years 1944-1946, as head of the temporary government, he made sure that Republican principles constituted the foundations of the post-war France. De Gaulle developed the state model of economy and the social character of the French republic. His decisions laid the Republican principles in the French Constitution and refer clearly to the Declaration of Human and Civil Rights of 1989 in both French post war constitutions. That is why the 5th Republic could only be established as an institutional variation within the framework of the Republican axiology.